The breath of the gods : the history and future of the wind - Winchester, Simon (Harper, an imprint of HarperCollinsPublishers, 2025)
"What is going on with our atmosphere? The headlines are filled with news of devastating hurricanes, murderous tornadoes, and cataclysmic fires affecting large swaths of America. Gale force advisories are issued on a regular basis by the National Weather Service. In 2022, a report was released by atmospheric scientists at the University of Northern Illinois, warning that winds--the force at the center of all these dangerous natural events--are expected to steadily increase in the years ahead, strengthening in power, speed, and frequency. While this prediction worried the insurance industry, governmental leaders, scientists, and conscientious citizens, one particular segment of society received it with unbridled enthusiasm. To the energy industry, rising wind strength and speeds as an unalloyed boon for humankind--a vital source of clean and "safe" power. Between these two poles--wind as a malevolent force, and wind as savior of our planet--lies a world of fascination, history, literature, science, poetry, and engineering which Simon Winchester explores with the curiosity and vigor that are the hallmarks of his bestselling works. In The Breath of the Gods, he explains how wind plays a part in our everyday lives, from airplane or car travel to the "natural disasters" that are becoming more frequent and regular. Between these two poles--wind as a malevolent force, and wind as savior of our planet--lies a world of fascination, history, literature, science, poetry, and engineering which Simon Winchester explores with the curiosity and vigor that are the hallmarks of his bestselling works. In The Breath of the Gods, he explains how wind plays a part in our everyday lives, from airplane or car travel to the "natural disasters" that are becoming more frequent." -- Dust jacket